Erythropoietin Receptor/β Common Receptor: A Shining Light on Acute Kidney Injury Induced by Ischemia-Reperfusion - Wu, Yuanyuan; Yang, Bin (Frontiers in Immunology, 2021)
Acute kidney injury (AKI) is a health problem worldwide, but lack of early diagnostic biomarkers and target specific treatments. Ischemia-reperfusion (IR), a major cause of AKI, not only induces kidney injury, but also stimulates self-defense system such as innate immune responses to limit injury. One of these responses is the production of erythropoietin (EPO) by adjacent normal tissue, which is simultaneously triggered, but behind the action of its receptors, either homodimer EPO receptor (EPOR)2 mainly involving in erythropoiesis or heterodimer EPOR/β common receptor (EPOR/βcR) having a broad range of biological protections. EPOR/βcR is expressed in several cell types including tubular epithelial cells at low level or absent in normal kidneys, but swiftly upregulated by hypoxia and inflammation and also translocated to cellular membrane post IR. EPOR/βcR mediates anti-apoptosis, anti-inflammation, pro-regeneration and remodeling via PI3K/Akt, STAT3 and MAPK signaling pathways in AKI. However, the precise roles of EPOR/βcR in the pathogenesis and progression of AKI have not been well defined, and its potential as an earlier biomarker for AKI diagnosis and monitoring repair or chronic progression requires further investigation. Here, we review biological functions and mechanistic signaling pathways of EPOR/βcR in AKI, and discuss its potential clinical applications as a biomarker for effective diagnosis and predicting prognosis, as well as directing cell target drug delivery.